Altered epidermal lipid processing and calcium distribution in the KID syndrome mouse model Cx26S17F - Bosen, Felicitas (FEBS Lett, 2015)
The keratitis–ichthyosis–deafness (KID) syndrome is caused by mutations in the gap junctional channel protein connexin 26 (Cx26), among them the mutation Cx26S17F. Heterozygous Cx26S17F mice resemble the human KID syndrome, i.e. exhibiting epidermal hyperplasia and hearing impairments. Newborn Cx26S17F mice show a defective epidermal water barrier as well as altered epidermal lipid secretion and location. Linoleoyl ω-esterified ceramides are strongly decreased on the skin surface of Cx26S17F mice. Moreover, the epidermal calcium gradient is altered in the mutant mice. These alterations may be caused by an abnormal Cx26S17F channel function that leads to a defective epidermal water barrier, which in turn may trigger the hyperproliferation seen in the KID syndrome.